2022
DOI: 10.1159/000527333
|View full text |Cite
|
Sign up to set email alerts
|

Cabergoline-Induced Hypoprolactinemia May Attenuate Cardiometabolic Effects of Atorvastatin: A Pilot Study

Abstract: Introduction: Hypoprolactinemia, which is usually a consequence of treatment with inadequate high doses of dopaminergic agents, is poorly understood clinical condition. The aim of the current study was to investigate whether cardiometabolic effects of statin therapy differ between patients with low prolactin production and patients with normal levels of this hormone. Methods: We studied two groups of cabergoline-treated premenopausal women with hypercholesterolemia matched for age, plasma lipids, cabergoline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Evidence showed that nuclear receptor REV‐ERBα modulated TH expression through binding to the TH promoter. REV‐ERBα is a direct transcriptional target of BMAL1 that is suppressed in the Bmal1‐KO brain 37 . Therefore, Bmal1 deficiency will decrease REV‐ERBα and TH expression and finally attenuate DA production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence showed that nuclear receptor REV‐ERBα modulated TH expression through binding to the TH promoter. REV‐ERBα is a direct transcriptional target of BMAL1 that is suppressed in the Bmal1‐KO brain 37 . Therefore, Bmal1 deficiency will decrease REV‐ERBα and TH expression and finally attenuate DA production.…”
Section: Discussionmentioning
confidence: 99%
“…REV-ERBα is a direct transcriptional target of BMAL1 that is suppressed in the Bmal1-KO brain. 37 Therefore, Bmal1 deficiency will decrease REV-ERBα and TH expression and finally attenuate DA production. On the other hand, a recent study revealed that Bmal1 deletion rendered the neurons more vulnerable to oxidative stress, which specifically manifested as TH neuron loss and cell-autonomous dopaminergic neurodegeneration.…”
Section: Suppression Of Prl Levels or Increasing Pg Levels Partially ...mentioning
confidence: 99%
“…This dimorphism in atorvastatin action was also observed in previous studies carried out by our research team. Although the drug was found to have a neutral effect on 25-hydroxyvitamin D levels in subjects with autoimmune thyroiditis [11,35], the treatment improved vitamin D status in women without endocrine abnormalities [36] or with non-classic congenital adrenal hyperplasia [37]. Statin-induced inhibition of HMG-CoA reductase may lead to an increase in 7-dehydrocholesterol, providing a substrate for the synthesis of 25-hydroxyvitamin D [38].…”
Section: Discussionmentioning
confidence: 99%
“…All reported cases of IPRLD described in literature concerned women, and the condition was revealed by a lactation failure occurring after delivery (puerperal alactogenesis). To date, in men and in non-lactating and non-pregnant women, PRL deficiency has no clinical implications, even if recent data have demonstrated an apparent impaired sexual functioning, reduced wellbeing and increased cardiometabolic risk in patients with iatrogenic IPRLD ( 219 ).…”
Section: Isolated Prolactin Deficiencymentioning
confidence: 99%